An Analysis of Students’ Low Confidence in Speaking, As the Attribute of Pronunciation Context - Karmida Karmida; Ahmad Laud Hasibuan; Nurlaili Nurlaili (UIBU, 2024)
Speaking requires mastering the vocabulary and pronunciation of the language well. The objective of this study is to find out the causes of students’ error in pronunciation and the students’ treatment in controlling their low confidence in speaking, to know the significant reasons of the phenomenon occurs. It is significantly influencing the developing of self-confidence and fluency in English. A mixed-methods approach used as research design. The subject of this research is students of English department who has problem in speaking. The data showed that students’ low confidence was caused by the problem of pronunciation. The biggest factor of students’ error in pronunciation is lack of practice and low motivation. The students had challenged about finding friends who can directly speak English. Another aspect also touches about the surrounding environment uses regional languages ​​and speaks Indonesian who prevent them to practice English. This study proved that low quality in English pronunciation caused low in English Speaking Competency. The study found some causes of students’ errors in English pronunciation, namely; Phonological Interference from Native Language, Lack of Exposure to Native English, Insufficient Pronunciation Practice, Teaching Methods and Materials, Psychological Factors.